The Novel, Volume 2 Forms and Themes - Moretti, Franco; Moretti, Franco (Princeton University Press, 2022)
Nearly as global in its ambition and sweep as its subject, Franco Moretti's The Novel is a watershed event in the understanding of the first truly planetary literary form. A translated selection from the epic five-volume Italian Il Romanzo (2001-2003), The Novel's two volumes are a unified multiauthored reference work, containing more than one hundred specially commissioned essays by leading contemporary critics from around the world. Providing the first international comparative reassessment of the novel, these essential volumes reveal the form in unprecedented depth and breadth--as a great cultural, social, and human phenomenon that stretches from the ancient Greeks to today, where modernity itself is unimaginable without the genre. By viewing the novel as much more than an aesthetic form, this landmark collection demonstrates how the genre has transformed human emotions and behavior, and the very perception of reality. Historical, statistical, and formal analyses show the novel as a complex literary system, in which new forms proliferate in every period and place. Volume 2: Forms and Themes, views the novel primarily from the inside, examining its many formal arrangements and recurrent thematic manifestations, and looking at the plurality of the genre and its lineages. These books will be essential reading for all students and scholars of literature.